Bitara gen. nov. of Tropiduchidae (Hemiptera: Fulgoromorpha) east of Wallace line - Stroiński, Adam; Szwedo, Jacek (Zootaxa, 2021)
A new genus and species of the tropiduchid planthopper of the tribe Tropiduchini is described as Bitara augusta gen. et sp. nov. from Madang Province, Papua New Guinea. It is the 18th species of Tropiduchini and the 9th genus known east of the Wallace line. It is another taxon with characteristic asymmetric genitalia within this tribe.